Status Kecepatan dan Kelincahan Pemain Black Panther fC Kota Malang - Mohammad Riza Firmansyah; Slamet Raharjo; Nanang Tri Wahyudi (Jurnal Ilmiah Adiraga, 2023)
The purpose of this study was to find out about the status of speed and agility of Black Panther Fc futsal players in Malang. The method in this study uses quantitative descriptive. The population in this study is futsal players Black Panther Fc Malang city. The sample in this study amounted to 20 players. Based on demographic data, it can be known that the mean, median, and mode of futsal players found the following results: mean age is 21 years, mean height is 168.8 cm, and dmean weight is 63.4 kg. Furthermore, the median age of futsal players is 21 years, and the median height is 168 cm, the median body weight is 60 kg. Finally, the age mode of futsal players is 20 years, the height mode is 167 cm, and the weight mode is 54 kg. The results of the speed test were "very good" 2 players, "good" 1 player, "enough" 2 players, and "less" 15 players who used the 30 m sprint test and for the results of the agility test were the results of "very good" 1 player, "good" 15 players, "enough" 1 player, and "less" 3 players using the Illinois agility run test. Overall, it can be concluded that the speed status is in the less category, while agility is included in the good category of Black Panther futsal players in Malang. Keywords: speed, agility, futsal,black panther fc malang city